Program Pengembangan Sumber Daya Manusia : Analisis Tren dan Dinamika Melalui Penelitian Global - Elivia Pasma Putri (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
Human resources are all assets related to individuals working in an organization. A human resources development program is a series of knowledge and activities specifically designed by each organization to empower humans as the main actors driving the organization. The author's research aims to determine the trends and dynamics of HR development programs through global research. The method used is simple quantitative research that focuses on general searches through the Scopus page, cluster selection on the Scival platform, and bibliometric research. The author takes the perspective of one cluster in selecting research trends related to human resources development programs, namely in the Assessment Center in Talent Management Practices. The results of the study: 130 scientific papers have been found in the Scopus platform. Meanwhile, the results of bibliometric research through VOSviewer found that the trends and dynamics of the topic have developed quite significantly and are more modern by providing discussions, such as "effectiveness," "evaluation," and "HRD programs" with a publication temporal of the 2020s and above. The research on Human Resources Development Programs from a global perspective encourages the development of science in the field of human resources management.